Enriching a building typology with data on heating systems and renovation measures. A case study from Hamburg. - Köhler, Ev (My University, 2017)
This paper examines 1.500 energy certificates of residential buildings from the city of Hamburg to derive frequencies on typical heating systems currently operating in the building stock and their proposed replacements for an energetic renovation in context of public incentive programmes. It was not possible to find a significant correlation between heating systems and IWU building types or heating systems and building's construction epochs in general. Yet, differences between heating systems in different construction types were found (for example multi-family buildings have a higher tendency to be connected to a district heating grid than single-family buildings). Furthermore, the frequencies of the considered heating systems within Hamburg's seven districts were derived from the dataset and may form a foundation for heat simulations on district- or city-scale. Additionally, this paper delivers coefficients that display the correlation of final energy demand for different heating systems and allow the comparison of the system's efficiency within one energetic level, the baseline condition, "usual" or "advanced" refurbishment level. The final energy demand computations are based on the TABULA Calculation Tool developed by the IWU with adjustments on the heating system according to the findings of the dataset examinations. In the end, an estimation of refurbishment costs, based on another publication of the IWU, complete the data for residential buildings and enable a holistic assessment of refurbishment measures in residential including the ecological and economical criterions.
Keywords: Bebauung; Gebäude; Energie; Wärme; Energieverbrauch; Heizung; Heizungssystem; Leistungsfähigkeit; Wärmebedarf; Gebäudetyp; Wohngebäude; Sanierungsmaßnahme; Sanierungskosten; Bewertungsmethode; Energieeffizienz; Bestandsgebäude; Gebäudebestand